The British Parliamentary Labour Party and the Government of Ireland Act 1920. (14th May 2013) - Gibbons, Ivan
Abstract : Immediately after the First World War the British Labour Party was forced to reconsider its relationship with an increasingly militant Irish nationalism. This reassessment occurred at the same time as it was becoming a major political and electoral force in post‐war Britain. The political imperative from the party's perspective was to portray itself as a responsible, moderate and patriotic alternative governing party. Thus it was fearful of the potential negative impact of too close an association with, and perceived sympathy for, extreme Irish nationalism. This explains the party's often bewildering changes in policy on Ireland at various party conferences in 1919 and 1920, ranging from support for home rule to federalism throughout the United Kingdom to 'dominion home rule' as part of a wider evolving British Commonwealth to adopting outright ' self‐determination' for a completely independent Ireland outside both United Kingdom and empire. On one aspect of its Irish policy, however, the party was adamant and united – its opposition to the partition of Ireland, which was the fundamental principle of Lloyd George's Government of Ireland Bill of 1920 which established Northern Ireland. Curiously, that aspect of Labour's Irish policy was never discussed in the party at large. All the running was made by the Parliamentary Labour Party (PLP) in the house of commons in 1920. The PLP's outright opposition to the bill acted as balm throughout the wider party, binding together the confusing, and often contradictory, positions promulgated on the long‐term constitutional future of Ireland and its relationship with Britain.